2017
DOI: 10.13168/cs.2017.0022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characteristics of Magnesium and Zinc Doped Hydroxyapatite Whiskers

Abstract: Mg and Zn doped hydroxyapatite whiskers were successfully prepared by hydrothermal homogeneous precipitation using amide additives. The morphology and structure of the products were characterized using SEM, XRD, and FTIR. It

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Previous studies regarding magnesium-doped hydroxyapatite have revealed that Mg ions inhibited the HAp crystallization in solution, and also that Mg in high concentrations could destabilize the structure of HAp [35,36]. Furthermore, studies have emphasized that Mg addition exhibited an inhibitory effect on HAp nucleation, its crystal growth, and also that Mg in high concentration causes a significant reduction in crystallinity coupled with an increase of its dissolution [37,38,39,40,41]. The complex investigation study of physico-chemical properties of hydroxyapatite doped with magnesium in solution [2,3,9,14,17] are rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies regarding magnesium-doped hydroxyapatite have revealed that Mg ions inhibited the HAp crystallization in solution, and also that Mg in high concentrations could destabilize the structure of HAp [35,36]. Furthermore, studies have emphasized that Mg addition exhibited an inhibitory effect on HAp nucleation, its crystal growth, and also that Mg in high concentration causes a significant reduction in crystallinity coupled with an increase of its dissolution [37,38,39,40,41]. The complex investigation study of physico-chemical properties of hydroxyapatite doped with magnesium in solution [2,3,9,14,17] are rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there are several emerging cations with both antimicrobial properties and important roles in the enhancement of the biological interactions of HAp with the surrounding tissues, amid which Mg 2+ comes into prominence [28][29][30]. Magnesium is one of the most important essential trace elements, being involved in the development of bones and connective tissues and possessing osteogenic and angiogenic stimulating properties, demonstrated both in vitro and in vivo [31][32][33][34][35]. Moreover, it has been reported that this specific trace element plays a significant role in the bone calcification process, influencing the osteoblast and osteoclast activities [32].…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Increased cell unit parameters are justifiable in consideration of enhanced content of lattice H 2 O confirmed with FTIR peaks at 3570-3572 cm -1 . 32 At a higher level of Cu incorporation (7% wt), dehydroxylation of materials might lead to a small decrease in a parameter expansion. 33 XRD spectra demonstrated the existence of nHA, Cs, and Gel components within scaffolds.…”
Section: Discussionmentioning
confidence: 99%